BIOLOGICAL CONTROL OF ð˜›ð˜¦ð˜µð˜³ð˜¢ð˜¯ð˜ºð˜¤ð˜©ð˜¶ð˜´ ð˜¶ð˜³ð˜µð˜ªð˜¤ð˜¢ð˜¦ KOCH (ACARI: TETRANYCHIDAE) WITH THE FUNGUS ð˜‰ð˜¦ð˜¢ð˜¶ð˜·ð˜¦ð˜³ð˜ªð˜¢ ð˜£ð˜¢ð˜´ð˜´ð˜ªð˜¢ð˜¯ð˜¢ (BALS.) VUILL., ON GRAPEYARD - Pereira, Rosylaine Aparecida; Bocalon Segantini, Ricardo; Corte CÃ¢mara, Igor; Arantes Pereira, Marcelo Francisco (REVISTA DE AGRICULTURA, 2021)
The spider mite, (Tetranychus urticae), causes considerable damage in a large number of crops in Brazil. In the grape, the species causes serious damage to the leaves, with necrosis and premature fall, damaging the photosynthesis of the plant and consequently the production and quality of the fruits. The control of the spider mite is carried out predominantly in a chemical way, whose environmental impact can be significant. The incorporation of biological methods would reduce the legal, environmental and public risks of the use of chemical products, mainly for the in natura. In order to provide an alternative strategy to control the T. urticae to grapeyard in the northwest region of São Paulo, the study aimed to evaluate the viability of biological control through the use of the pathogenic fungus Beauveria bassiana under the conditions local climatic conditions under different dosages. They were sprayed in a vineyard area of the BRS-Vitória variety in Palmeira d'Oeste/SP, four combinations of products based on B. Bassiana, with and without mineral oil, in addition to a treatment containing only mineral oil, which were compared with the control in relation to the effect on eggs and adults of the spider mite and also its effects on their mortality. No significant results of the application of B. bassiana on the occurrence of eggs and adults of T. urticae were observed, even with the addition of mineral oil. However, there were positive results of the fungus application on mite mortality. Longer evaluation periods could provide better efficiency results.